Duration-dependent impact of cardiometabolic diseases and multimorbidity on all-cause and cause-specific mortality: a prospective cohort study of 0.5 million participants - Han, Y; Hu, Y; Yu, C; Sun, D; Pang, Y; Pei, P; Chen, Z; Yang, L; Chen, Y; Du, H; Liu, J; Schmidt, D; et al. (BioMed Central, 2023)
Background The association of incident cardiometabolic multimorbidity (CMM) with mortality risk is rarely studied, and neither are the durations of cardiometabolic diseases (CMDs). Whether the association patterns of CMD durations with mortality change as individuals progress from one CMD to CMM is unclear.